ANALISIS KOMPETENSI PEDAGOGIK GURU TERHADAP PENGUNAAN MEDIA PEMBELAJARAN BAHASA ARAB KELAS VIII DI MTS AL-KHAIRAT WOSU KABUPATEN MOROWALI - Siti Hasnah; Hardianti (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2021)
The research is descriptive qualitative research. The purpose of this study was to determine the effect of pedagogic competence on the use of Arabic learning media. Data collection techniques used are observation, interview, and documentation techniques. The data analysis technique used is data reduction, data presentation, and conclusion drawing, as well as checking the validity of the data. Sources of data obtained from primary and secondary data that are relevant to the problem under study. The results of this study indicate that the pedagogic competence of teachers at MTs al-Khairaat Wosu can be said to be quite good. This is evidenced from the results of research on related indicators, in the form of lesson planning, learning implementation, and learning evaluation, also seen from the attitude of teachers who have understood the characteristics of their students so that they can develop good learning implementation plans according to the needs of students. Second, pedagogic competence influences the use of learning media. This can be seen from teachers who have good pedagogic competence, use good learning media in the learning process so that learning objectives can be achieved.